ChemInform Abstract: One‐Pot Synthesis of 5‐Hydroxy‐4H‐1, 3‐thiazin‐4‐ones: Structure Revision, Synthesis, and NMR Shift Dependence of Thiasporine A. Issue 46 (October 2016) - Seitz, Tobias; Fu, Peng; Haut, Franz‐Lucas; Adam, Lutz; Habicht, Marija; Lentz, Dieter; MacMillan, John B.; Christmann, Mathias
Abstract: The annulation of arylthioamides, which may be applied to alkylthioamides, with 3‐bromopyruvic acid chloride is investigated offering access to the proposed structure of thiasporine A [cf.